2010
DOI: 10.4049/jimmunol.1000680
|View full text |Cite
|
Sign up to set email alerts
|

Eye Mucosa: An Efficient Vaccine Delivery Route for Inducing Protective Immunity

Abstract: The external part of the eye shares mucosa-associated common characteristics and is an obvious entry site for foreign Ags. We assessed the potential of eyedrop vaccination for effective delivery of vaccines against viral or bacterial infection in mice. Both OVA-specific IgG Ab in serum and IgA Ab in mucosal compartments were induced by eyedrops of OVA with cholera toxin (CT). Eyedrop vaccination of influenza A/PR/8 virus (H1N1) induced both influenza virus-specific systemic and mucosal Ab responses and protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 41 publications
2
58
0
1
Order By: Relevance
“…Eyedrop administration of protein Ag, influenza virus and attenuated bacteria stimulated a broad range of Ag-specific systemic and mucosal immune response, influenza-virus specific systemic and mucosal humoral immune response, and systemic LPS-specific humoral immune response followed by complete protection against pathogen lethal challenge, respectively (Seo et al, 2010). In the present study, we investi- Table 2 Stimulation of primary HCDECs with BGs significantly increase expression of ICAM-1.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Eyedrop administration of protein Ag, influenza virus and attenuated bacteria stimulated a broad range of Ag-specific systemic and mucosal immune response, influenza-virus specific systemic and mucosal humoral immune response, and systemic LPS-specific humoral immune response followed by complete protection against pathogen lethal challenge, respectively (Seo et al, 2010). In the present study, we investi- Table 2 Stimulation of primary HCDECs with BGs significantly increase expression of ICAM-1.…”
Section: Discussionmentioning
confidence: 91%
“…The excellent delivery capacity of BGs, ability to stimulate cytokine secretion by target cells, and capability to increase expression of co-stimulatory molecules on the surface of target cells emphasize BGs as a promising candidate for ocular surface disease treatment. Recent study showed that eyedrop administration of target Ag using attenuated bacterial model efficiently induces both bacterial strain LPS-specific and Ag-specific immune responses without changes of behavior, body weight, and local inflammation in tested animal (Seo et al, 2010). We are aware that using Gram-negative bacteria LPS content of the cell envelopes presented on the BG's shell does not represent a risk for using of BGs as a potential drug delivery candidate (Paukner et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…This is of special importance, as the eye mucosa shares several immunological features with other mucosal compartments, and as such, the use of eyedrop vaccination against influenza virus is under investigation as an alternative vaccine strategy capable of inducing protective immunity. 58,59 …”
Section: Ocular Tropism Can Be Measured In the Laboratorymentioning
confidence: 99%
“…However, this certain drawbacks associate with this route are poor drainage of instilled solutions, tear turnover, poor corneal permeability, metabolism (enzymatic degradation) and low capacity for transport, nasolacrimal drainage, and systemic absorption. Eye drop vaccination of influenza A/PR/8 virus (H1N1) induced both influenza virus-specific systemic and mucosal Ab responses and protected mice completely against respiratory infection with influenza A/PR/8 virus (Seo et al 2010). Ocular mucosal delivery of peptide epitopes of herpes simplex virus (HSV-1) glycoprotein D (gD) has mixed with oligodeoxy nucleotides containing unmethylated CpG motifs (CpG2007).…”
Section: Ocular Routementioning
confidence: 99%